Cost and Time Control of the Landikma Health Center Project Using Earned Value - Jansen, Davy Ivan Robert; Erwin, Erwin (ASTONJADRO, 2026)
The construction project of the Landikma Community Health Centre in Yalimo Regency was scheduled to be completed within 23 weeks with a contract value of IDR 23,310,500,000.00. With time and cost constraints, good and thorough control was required. However, before control could be implemented, it was necessary to first determine the performance of the project that had been underway. The purpose of this study is to determine the cost and time performance, cost and time estimates at the end of the project completion, and the factors that cause project delays or progress. The method used in this study is the Earned Value Analysis method, which combines cost and time elements as well as physical work performance. The data obtained from the project included the project time schedule, budget plan (RAB), weekly project reports and actual costs. This was followed by an analysis of costs, schedules, variances and performance indices, highlighting the issues that arose during the research. The analysis results show that the costs incurred were lower than the budgeted costs, as indicated by a CPI value of 1.50, and the implementation time was slower than the planned schedule, as indicated by an SPI value of 0.81. The final project cost estimate was calculated at IDR 16,514,712,233.33 with an estimated completion time of 41 weeks, indicating that the project was 18 weeks behind the planned 23 weeks. This delay was caused by various factors, such as delays in the initial piling of the project by third parties, equipment damage, changes to the drawings by the planning consultant, design changes by the owner, the difficulty of the terrain leading to the location, limited availability of materials and equipment, and unfavourable field conditions due to riots.